Student Response System in Dental Students’ Education. Using a Student Response System and Peer Discussion to Raise the Awareness of the Importance of Good Professional Communication Skills in Practice Periods - Rune Johan Krumsvik; Lise Øen Jones; Kristin S. Klock (Designs for Learning)
In large lectures in education of dentists there is often less dialogue and communication between students and the instructors, and several studies have found that traditional lecturing in such lectures is ineffective in promoting student learning. This Design Based Research (DBR) and case presentation focus on how the use of Student Response Technology (SRS) and feedback can improve communication in large lectures in dentist education. The case presentation is based on lecturer’s experiences and student responses from ten annual large lectures from the period 2010-2019 in the course “Practice Study” (3 ECTS) at University of Bergen where dentist students and their supervisors were gathered for an annual one-day seminar. The case presentation shows the importance of recognizing the factors that affect dentist students’ nervousness and tension for the practice periods and where the use of SRS seems to contribute to raise the awareness among supervisors and students about such issues. This, and a focus on good communications skills among dentist students and their supervisors seems to be crucial to focus on before their practice period in The Public Dental Health Care. There are also a number of limitations in this case presentation, which will be handled in the further development of this DBR-project.